Foreign policy change in Brazil: Drivers and implications - Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2022)
Even during his 2018 election campaign, Jair Bolsonaro promised a fundamental shift in Brazilian foreign policy. Since taking office as Brazil's president on 1 January 2019, foreign policy change has been ever present in Bolsonaro's discourse and, in some cases, is evident in policy decisions. Foreign policy change is not just about modified rhetoric, but rather about a targeted policy with ideational foundations and supporting actors. The change is being driven by members of the government's so-called ideological wing. Some of the shifts that have already taken place during this political change should be seen less as a break with the policies of the previous government than as an intensification of developments that had already been underway for several years. Some foreign policy goals of the ideological wing fail because of the interests and interventions of the other two government wings, the technocratic and the military wing. Several contextual factors, such as China's growing economic importance, also delimit the sought after foreign policy change.
Keywords: 320; Brazil; Jair Bolsonaro; Itamaraty; ideological wing; Ernesto Araújo; BRICS; IBSA; Evangelicals